2016
DOI: 10.7196/samj.2016.v106i8.10124
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to female genital mutilation/cutting among male adolescents in Ilorin, Nigeria

Abstract: Education and involvement in advocacy may transform male adolescents into agents for eradication of FGM/C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Additionally, in the study [10][11][12], a major concern was that most male teachers perceived FGM as a religious obligation to circumcise their daughters in the future. However, in the study [10], the findings concerning FGM and religion is that it is found across all types of religion. It is not an obligation for any particular religion.…”
Section: Description Of the Studies Includedmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in the study [10][11][12], a major concern was that most male teachers perceived FGM as a religious obligation to circumcise their daughters in the future. However, in the study [10], the findings concerning FGM and religion is that it is found across all types of religion. It is not an obligation for any particular religion.…”
Section: Description Of the Studies Includedmentioning
confidence: 99%
“…"FGM is a tradition in transition". FGM is majorly performed by the traditional practitioners, however, there have been cases were FGM was performed by the health workers [8][9][10]. This is referred to as medicalization of FGM.…”
Section: Introductionmentioning
confidence: 99%
“…The articles were published between 1978 and 2021 (22 August), with only two studies before 2000 (one article was published in 1978, and one in 1997). With regard to the FGM/C participants of the 40 studies, ten studies were conducted among health care professionals [ 21 , 23 , 31 , 34 , 35 , 36 , 41 , 45 , 50 , 51 ], eight were conducted among women from the general population [ 20 , 22 , 24 , 27 , 29 , 47 , 49 , 52 ], nine were conducted among students [ 10 , 17 , 30 , 32 , 33 , 38 , 40 , 43 , 46 ], four were conducted among a general population in which no distinction was made between men and women [ 26 , 28 , 48 , 53 ], four were conducted among circumcised women [ 18 , 19 , 39 , 42 , 54 ], one was conducted among online users [ 44 ], one was conducted among pregnant women [ 25 ], one among patients in hospitals [ 37 ], and one study was conducted among school teachers [ 16 ]. The sample sizes of participants varied from 63 to 21,756, with a total sample size of 184,574 participants.…”
Section: Resultsmentioning
confidence: 99%
“…The age of the participants ranged between 15 and 60 years. The participants from the included studies were from 16 different countries or regions, including Egypt [ 10 , 18 , 19 , 24 , 29 , 32 , 43 , 47 , 53 ], Nigeria [ 16 , 17 , 20 , 25 , 40 , 41 , 50 ], Ethiopia [ 27 , 46 , 52 ], Sudan [ 21 , 28 , 30 , 38 , 48 ], Iraq [ 49 ], Australia [ 45 ], Kenya [ 37 , 42 , 54 ], USA [ 31 ], Yemen [ 22 ], Belgium [ 23 , 36 ], Gambia [ 33 , 34 ], Guinea [ 26 ], various African countries, [ 26 ] Middle East countries, [ 44 ], Iran [ 51 ], and Tanzania [ 39 ]. All studies used a cross-sectional design, and 11 of them were obtained from national Demographic and Health Survey (DHS) studies, like the Department of International Development Sudan Opinion Poll (DFIDSOP) dataset [ 28 ], Yemen Demographic and Health Survey (YDHS) [ 22 ], Egypt Demographic and Health Survey (EDHS) [ 19 , 24 , 47 ], Kenya...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation